Family Businesses in Cities of Indonesia: Analysis and Proposed Business Strategy Using TOWS Matrix - Kurnia, Mohammad Ikhsan; Amrullah, Yusuf Amri (Forum Bisnis Kewirausahaan, 2024)
Family businesses are an integral part of the urban economic landscape in Indonesia. However, family businesses face unique challenges that often befall them, namely issues of business continuity, succession, professionalism, family conflict, financial performance and ownership. Using a qualitative approach and literature review methods, this research was conducted to search for and analyze academic literatures about family businesses in cities of Indonesia, then researchers formulated proposed strategies to face the challenges using TOWS Matrix. Keywords: Business, Family, City, TOWS